A Virtual Reality Game to Assess OCD Symptoms - van Bennekom, Martine J.; de Koning, Pelle P.; Gevonden, Martin J.; Kasanmoentalib, M. Soemiati; Denys, Damiaan (Frontiers in Psychiatry, 2021)
Background Symptoms of obsessive-compulsive disorder (OCD) are often underreported by patients and mainly triggered in the patients private domain, making it harder for clinicians to recognize OCD. Virtual reality (VR) can be used to assess OCD symptoms in the clinician’s office. We developed a VR game in order to provoke subjective and physiological OCD symptoms. We hypothesize that (1) the VR game provokes more OCD symptoms in patients compared to healthy controls, (2) performing virtual compulsions leads to a reduction in emotional responses in OCD patients and that (3) the severity of VR game provoked symptoms correlates with severity of OCD symptoms. Methods Participants played the VR game on a laptop while physiological measures were recorded simultaneously. We measured emotional responses, virtual compulsions and physiological arousal in response to our VR game in 26 OCD patients and 26 healthy controls. We determined correlations between emotional responses, virtual compulsions and OCD severity. Results We found higher levels of VR-provoked anxiety (U=179.5, p=0.004) and virtual compulsions in OCD patients compared to healthy controls (p=0.001). There was a significant reduction in emotional responses after performing virtual compulsions in the OCD patients. The emotional responses and virtual compulsions did not correlate significantly with Y-BOCS scores. A baseline difference between patients and healthy controls was found in heart rate variability (HRV), but no significant change in HRV, heartrate and skin conductance was found during the VR game Conclusions Our study clearly shows our OCD VR game is capable of provoking more anxiety and virtual compulsions in patients with OCD compared to healthy controls. Providing a direct patient-rated measurement in the clinicians room. the VR game could help in assessing core OCD symptoms and recognizing OCD